2022
DOI: 10.3389/fmed.2021.778474
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for the Prevention of Postoperative Cognitive Dysfunction Among Older Adults Undergoing Hip and Knee Arthroplasty: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Postoperative cognitive dysfunction (POCD) is a common surgical complication in elderly patients undergoing hip and knee replacement. Electroacupuncture (EA) may have a protective effect on postoperative cognitive function, but relevant evidence remains uncertain.Objective: To systematically evaluate the evidence of EA for the prevention of POCD after total joint arthroplasty.Methods: PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), China National Knowledge Infrastructure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For osteoarthritis, a common orthopedic disease with a sharp increase in the number of resulting fractures, TKA is undoubtedly an ideal treatment [ 20 ]. TKA is mostly performed in the elderly who are at an increased risk of perioperative cognitive dysfunction due to poor physical condition and fragile physiological function of the nervous system [ 21 ]. On the other hand, TKA patients may have varying degrees of coagulation function changes, which is one of the pathological causes of DVT [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For osteoarthritis, a common orthopedic disease with a sharp increase in the number of resulting fractures, TKA is undoubtedly an ideal treatment [ 20 ]. TKA is mostly performed in the elderly who are at an increased risk of perioperative cognitive dysfunction due to poor physical condition and fragile physiological function of the nervous system [ 21 ]. On the other hand, TKA patients may have varying degrees of coagulation function changes, which is one of the pathological causes of DVT [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of five randomized controlled trials has shown improvements in POCD with acupuncture, although the findings are often limited by biases in methodological quality ( Kim et al, 2019 ). Furthermore, a meta-analysis focused on the use of EA for preventing POCD in older adults who have undergone hip or knee arthroplasty has highlighted that EA pretreatment can be an effective intervention for improving cognitive outcomes ( Ou et al, 2021 ). In recent years, an increasing body of research has revealed the positive effects of EA in either preventing or addressing postoperative cognitive deficits observed in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically and experimentally, electroacupuncture (EA) exerts preventive effects against cognitive dysfunction in POCD models by controlling stimulation frequency and intensity [ 12 , 13 ]. Our group has previously found that EA improves cognitive decline following spine surgery in elderly patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%